Effect of verbal encouragement within circuit training on enhancing sport motivation and technical skills among elite cricket athletes - Basri, Hasan; Ridho, Azi Faiz; Haqiyah, Aridhotul; Bujang; Setiawan, Edi (Journal Sport Area, 2026)
Background: Evidence indicates that cricket match results depend on the quality of sport motivation (SM) and technical skills (TS) of elite athletes, and both aspects can be improved through coaches' verbal encouragement during circuit training (CVEdCT). However, limited research has examined the combined effect of verbal encouragement within structured circuit training on both psychological and technical outcomes in cricket. Objectives: Our study aims to examine the effect of CVEdCT on improving SM and TS. Methods: This study adopted an experiment with a pretest-posttest control group design. We involved 38 elite cricket athletes in this study. Overall, this study was conducted over a period of 9 weeks. The SM and TS aspects were measured at the pretest and posttest stages. Results: Our research results show that there is a time × group effect on the SM variable in all indicators of intrinsic motivation (p = 0.007), integrated regulation (p = 0.0012), external regulation (p < 0.001), amotivation (p = 0.010), and TS variables with indicators of batting accuracy (p < 0.001), bowling speed (p = 0.006), bowling accuracy (p < 0.001), and fielding efficiency (p = 0.024). Meanwhile, we observed a time effect on the indicators of intrinsic motivation (p = 0.002), integrated regulation (p = 0.031), external regulation (p = 0.013), and amotivation (p = 0.048). Additionally, the TS variable showed significant effects for the indicators of batting accuracy (p = 0.007), bowling speed (p = 0.003), bowling accuracy (p = 0.011), and fielding efficiency (p = 0.006). Based on the Poshoc Bonferroni analysis, there was a significant effect of both groups on SM and TS, but the increase was greater in CVEdCT than CTG. Conclusion: Thus, this study concludes that CVEdCT can improve SM and TS among elite cricket athletes better than CTG.